Análise de qualidade agronômica, físico-química e sensorial em couves de folha crespa cultivada com fertilizantes orgânicos - Pimenta, Daniella Martins (Universidade Federal de São Carlos, 2020)
The aim of this work was to evaluate the influence of organic fertilizers on the agronomic, physicochemical and sensory characteristics of curly kale (Brassica oleracea L. var. acephala, Darkibor). The treatments were: A, Control = without fertilization; B = with organomineral fertilizer and C, D and E = with organic fertilizers. The plants were evaluated sixty days after planting in relation to agronomic, physicochemical and sensory parameters. The data were analyzed by ANOVA, considering the level of significance (p≤0.05) and, when necessary, the Tukey’s test was applied, and for the ranking test, the Friedman’s test was employed. The organic and organomineral fertilization had a positive influence on petiole length, width and total number of leaves, plant height and leaf area, when compared to the control (A). For stem diameter, leaf length and chlorophyll content, there was no significant difference among the treatments. Regarding the physicochemical analyses, there was no significant difference among the treatments. The treatments met the Brazilian legislation for the microbiological analysis of the leaves. The sensory analyses of ranking and acceptability showed no difference among the treatments. In general, the use of organic and organomineral fertilizers promoted greater efficiency for the kale plants with regard to the agronomic characteristics.
Analysis of agronomic, physicochemical and sensory quality in curly Kale grown with organic fertilizer
Keywords: Brassica oleracea L. var. acephala; Qualidade; Minerais; Físico-química; Cor e aceitação; Quality; Minerals; Physicochemical; Color and acceptance; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::AVALIACAO E CONTROLE DE QUALIDADE DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::MICROBIOLOGIA DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::PADROES, LEGISLACAO E FISCALIZACAO DE ALIMENTOS; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::VALOR NUTRITIVO DE ALIMENTOS; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::FERTILIDADE DO SOLO E ADUBACAO; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::QUIMICA DO SOLO; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS; CIENCIAS DA SAUDE::NUTRICAO; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL::NUTRICAO E CRESCIMENTO VEGETAL; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA